2021
DOI: 10.1088/1361-6528/ac0ac7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crystal structure on the Young’s modulus of GaP nanowires

Abstract: Young's modulus of tapered mixed composition (zinc-blende with a high density of twins and wurtzite with a high density of stacking faults) Gallium Phosphide (GaP) nanowires (NWs) was investigated by atomic force microscopy (AFM). Experimental measurements were performed by obtaining bending profiles of as-grown inclined GaP NWs deformed by applying a constant force to a series of NW surface locations at various distances from the NW/substrate interface. Numerical modeling of experimental data on bending profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Another factor is attributed to the competition between the nucleation rate at the Pd-Ga droplet and at the substrate surface; when nucleation at the substrate surface dominates, parasitic GaP growth in the form of 2D layers, agglomerated particles, and/or 3D islands occurs. This substrate surface growth may hinder NW growth by changing the regular 〈111〉 growth directions to unfavourable new growth directions [52][53][54].…”
Section: Effect Of Nw Growth Parametersmentioning
confidence: 99%
“…Another factor is attributed to the competition between the nucleation rate at the Pd-Ga droplet and at the substrate surface; when nucleation at the substrate surface dominates, parasitic GaP growth in the form of 2D layers, agglomerated particles, and/or 3D islands occurs. This substrate surface growth may hinder NW growth by changing the regular 〈111〉 growth directions to unfavourable new growth directions [52][53][54].…”
Section: Effect Of Nw Growth Parametersmentioning
confidence: 99%
“…For GaP NWs grown by the MOVPE (ZB with high density of twinning defects) and MBE methods (WZ with high density of SFs), Prokhor A Alekseev et al reported a similar Young’s modulus (155 ± 20 GPa and 157 ± 20 GPa) or both types of NWs with the AFM method. Thus, they concluded that crystal structure (WZ/ZB) and crystal defects on the Young’s modulus of GaP NWs can be negligible [ 128 ].…”
Section: Structural–dependent–physical Properties Of Iii–v Nwsmentioning
confidence: 99%